2019
DOI: 10.1177/1550059419888338
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Source Connectivity in the Prediction of Electroconvulsive Therapy Outcome in Major Depressive Disorder

Abstract: Objectives. Major depressive disorder (MDD) is a common and potentially lethal disorder affecting up to 14% of all persons worldwide. However, one-third to thwo-thirds of patients are nonresponders to first-line therapy. Even the electroconvulsive therapy (ECT) as the option of choice in therapy-resistant MDD still shows a high proportion of nonresponders. In case of a predicted nonresponse to ECT, for example, by means of electrophysiological electroencephalogram (EEG) parameters, other therapies of MDD (eg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
1
7
1
Order By: Relevance
“…participants at baseline, with significantly decreased alpha and nominally decreased theta connectivity post-treatment in male responders only (50). In an electroconvulsive therapy (ECT) study, responders showed reduced resting-state alpha connectivity compared to non-responders (51). While these studies are not consistent with ours, the mechanism of action of each treatment is likely different.…”
Section: Discussioncontrasting
confidence: 52%
“…participants at baseline, with significantly decreased alpha and nominally decreased theta connectivity post-treatment in male responders only (50). In an electroconvulsive therapy (ECT) study, responders showed reduced resting-state alpha connectivity compared to non-responders (51). While these studies are not consistent with ours, the mechanism of action of each treatment is likely different.…”
Section: Discussioncontrasting
confidence: 52%
“…For example, a large EEG study by Iseger et al 62 showed reduced alpha connectivity in male responders to a trial of antidepressant medication (Escitalopram, Sertraline, or Venlafaxine-XR). Pre-treatment alpha, beta, and gamma band connectivity has also been shown to moderate antidepressant (sertraline hydrochloride or placebo) treatment outcome in a recent large multi-centre study using a novel power envelope connectivity approach 63 ; while lower pre-treatment alpha-band connectivity has been observed in responders to ECT 64 . Although further work is needed to better elucidate the underlying mechanisms responsible for the observed connectivity changes in the present study, a recently proposed connectivity resetting hypothesis 9 might aid in partially explaining these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding alpha 2 frequency band, Kirsten and colleagues found a lower linear connectivity in responders and a role of frontal left side associations and frontal interhemispheric correlations in clinical improvement. Results on alpha 1 frequency band were not significant ( 28 ). Stubbeman and colleagues found a significant association between the decrease in HDRS and central cordance; other regions and QEEG measures were not significant ( 26 ).…”
Section: Resultsmentioning
confidence: 92%
“…Three studies used EEG among other polysomnographic recordings ( 19 , 21 , 22 ). The oldest study, published in 1989, used EEG intermittent photic stimulation and hyperventilation ( 23 ), and the five other studies used eyes-closed resting-state EEG ( 24 28 ). Two eyes-closed EEG studies computed three-dimensional space with low-resolution electromagnetic tomography (LORETA) to analyze data.…”
Section: Resultsmentioning
confidence: 99%